64. Skin dose in high dose rate brachytherapy for breast cancers: evaluation by in vivo dosimetry using TLD and MOSFET dosimeters. (December 2018) - Fabiani, S.; Italiani, M.; Casale, M.; Muti, M.; Maranzano, E.
Abstract : Purpose: The aim of this work is to evaluate a novel approach for the verification of the real skin dose in partial breast high dose rate brachytherapy (PB-BRT), quantify the treatment planning system (TPS) overestimation and develop a methodology for routinary in vivo dosimetry (IVD). Methods: Currently there is not a general acknowledged constraint for skin dose in PB-BRT. Because of our center's experience (20 PB-BRT patients treated/year) we achieve a good cosmetic outcome if the TPS calculated skin dose is below 50% of the prescription of 32 Gy (4 Gy/fraction, twice daily). The skin dose was calculated by a TPS which overestimates it assuming a homogeneous water medium and not accounting for the finite patient dimensions. IVD was performed on patients treated with multi-catheter brachytherapy, which involves placement of 9–15 catheters through the breast. Thermoluminescent dosimeters (TLDs) were used in the IVD sessions and they were placed on the skin next to the catheters and the nipple. We are currently implementing MOSFET real time measurements to compare with TLD results and to further improve the estimation of the skin dose. Results: The doses measured by TLDs were compared to those calculated by the TPS in specific region of interest (ROI). For each patient two IVD sessions were performed, and the reproducibility of TLD positioning was assessed: 60% of couples give the same value within the experimental error. 77% of measurements show a clear overestimation of skin dose by the TPS. A Gaussian fit of the percentage differences between measured and calculated doses (Fig. 1) yielded an overestimation value of (25.2 ± 7.6)%. For a first group of patients IVD sessions were performed using MOSFET dosimeters, placed on the skin following the previous arrangement of TLDs. The doses measured by MOSFETs were compared to those calculated by the TPS in specific ROIs. Preliminary results show a quantitatively similar overestimation. Conclusions: Measurements in PB-BRT are necessary to quantify the real skin dose accurately. A novel approach based on IVD allows us to define dose limits, to achieve not only the tumor control but also a good cosmetic outcome to improve the quality of patient's life.